PERSEPSI DAN HARAPAN KONSUMEN TERHADAP KUALITAS PRODUK LAYANAN TRIPLE-PLAY INDIHOME PADA PT. TELKOM INDONESIA WILAYAH KOTA MAKASSAR - Fitriani Latief; Fika Yulianti M (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2019)
This study aims to determine whether there are differences in consumer perceptions and expectations of the quality of Indihome Triple-Play service product. This research was a survey research using a questionnaire. The population in this study were cunsumers of PT. Telkom Indonesia in Makassar City area and the sample were 100 respondents who have subscribed to Indihome Triple-Play. The data analysis and T test using IBM SPSS Statistics version 25. The results of this study indicate that the average consumer perceptions and expectations had no differences in performance, reliability and features, and there were significant differences (gap) in conformance to spesification and perceived quality toward the quality of Indihome Triple-Play service products.